Implementasi Peraturan Pemerintah Nomor 46 Tahun 2011 Tentang Penilaian Prestasi Kerja Pegawai Negeri Sipil - Pasaribu, Sarjani; Harahap, R. Hamdani; Mardiana, Siti (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2020)
The problem of this research is how to implement Government Regulation Number 46 Year 2011 on the appraisal of civil service performance especially at the Regional Office of Ministry of Law and Human Rights of North Sumatera. This research has been conducted since December 2018 until January 2019and has taken place at the Regional Office of Ministry of Law and Human Rights of North Sumatera. The Qualitative descriptive method is used in this research. Observation, interviewing and documentation are as data collection of this research. The main interviewees are the head of division of administration, the head of general department, the head of sub staffing department and ten (10) employees from each division to obtain detailed according to the need of the writer. The result of this research describes the implementation of the appraisal of civil service performance, based on government regulation Number 46 Year 2011at the Regional Office of Ministry of Law and Human Rights of North Sumatera has been implemented well.Â  The role of four (4) factors to successful policy implementation such as: 1. Communication, 2. Resources, 3. Disposition, 4. Structure of the bureaucracy can be fulfilled although it has not been perfect. The civil servants that become the policy target of the appraisal of civil service performance do not have any difficulties to obtain the information of the appraisal of civil service performance. The existing information has given the certainty to the civil servants of the describing the performance target of civil.